Disability as a fluid state - Barnartt, Sharon N. (Research in social science and disability ;, 2010)
Disability is often described in a way that suggests that it is most often a permanent state. Many concepts and models of disability suggest this. Even when it is described as being socially constructed, the implication is that an impairment leads to a permanent status of disabled within that social, cultural or historical milieu. But there is a lot of evidence that disability is a fluid state. The relationship between impairment (physical state) and disability is neither fixed nor permanent but is fluid and not easily predicted. This volume revolutionarily reconceptualizes disability not as a static but a dynamic phenomenon which is related to social, cultural, psychological and historical context. Papers by leading disability scholars in the areas of sociology, anthropology and history examine this premise from many points of view. Several look at micro-level interactional processes over time, some look at cultural change over time and their effects on definitions and measurements, and some look at how social processes shape physical conditions into disabilities or impairments/disabilities into normality. All examine the fluidity of disability and rethink how we measure it.